EFEKTIFITAS PEMBELAJARAN DARING PADA MASA PANDEMI COVID 19 DI MTs NEGERI 2 TOLITOLI - Nasriani Nasriani (Sekolah Tinggi Pariwisata Mataram, 2022)
This study aims to determine the effectiveness of online learning during the covid-19 pandemic at MTs Negeri 2 Tolitoli. This research is a descriptive qualitative research. The subjects in this study were the head of MTs Negeri 2 Tolitoli, one teacher in the field of study and three students. Data collection techniques are carried out through observation, interviews and documentation. Based on the results of the research above, it can be said that if you look at the results of observations that the implementation of online learning at MTs Negeri 2 Tolitoli has been carried out using online learning applications, namely whatsapp and google form. The advantage of online learning in this study is that it can carry out learning during the social distension period, in this case distance learning and the weakness of this learning is that there are several factors, namely problems with network or signal access, internet quotas and also application errors in its implementation.